Concussion information online: evaluation of information quality, content and readability of concussion-related websites - Ahmed, O. H.; Sullivan, S. J.; Schneiders, A. G.; McCrory, P. R. (British Journal of Sports Medicine, 2012)
Background: The internet plays an important role in the dissemination of health information to the general public. Information on orthopaedic sports medicine websites has been shown to be of a varying standard, and to date there has been no evaluation of the overall quality of concussion-related websites.